Atrezija hoan - prikaz primera - Žnidaršič, Marta (Medicinski razgledi, 2011)
Choanal atresia is a rare congenital malformation which occurs in every 5000 to 8000 live newborns. Clinically, it may present as an isolated form or in association with other malformations. In most cases, the cause is not found, but some are associated with a genetic mutation or the use of certain drugs agninst hyperthyroidism during pregnancy. The dominant clinical picture at birth is respiraiory distress with severe cyclic cyanosis. The paper presents the case of a girl with isolated bilateral choanal atresia who showed signs ofrespiratory distress and cyanosis at birth. The development of the nose and nasal cavity, the etiology, dinical picture, diagnostics, primary care, and surgical treatmeni of choanal atresia are discussed.
Keywords: Choanal Atresia; Hoana, atrezija; Etiology; Hipertiroidizem; Diagnosis; Dihalna stiska, sindrom; Cianoza; Therapy; Respiratory Distress Syndrome; Metimazol; Cyanosis; Novorojenček; nosna votlina; Hyperthyroidism; nos; Drug Therapy; malformacije; Methimazole; Adverse Effects; dihalna stiska; Infant, Newborn; zdravljenje; diagnostika